"Please tidy up before leaving": nudging Airbnb guests toward altruistic behavior. Issue 4 (25th October 2019) - Ranson, Paul; Guttentag, Daniel
Abstract : Purpose: This study aimed to investigate whether increasing the social presence within an Airbnb lodging environment could nudge guests toward altruistic cleaning behaviors. Design/methodology/approach: The study was based around a theoretical framework combining the social-market versus money-market relationship model, nudge theory and social presence theory. A series of three field experiments were conducted, in which social presence was manipulated to test its impact on guest cleaning behaviors prior to departure. Findings: The experimental results confirmed the underlying hypothesis that an Airbnb listing's enhanced social presence can subtly induce guests to help clean their rental units prior to departure. Originality/value: This study is the first to examine behavioral nudging in an Airbnb context. It is also one of the first field experiments involving Airbnb. The study findings offer clear theoretical and practical implications.